Self-crosslinking polymer, preparation method thereof, anion exchange membrane and application
By introducing fluorine atoms and flexible long alkyl side chains into the anion exchange membrane, a crosslinking network is formed, combining heat crosslinking and electron beam treatment, the trade between high ion conductivity and dimensional stability of the anion exchange membrane is solved- Off problem achieves efficient ion conduction and chemical stability, and is suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411328538.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The existing anion exchange membrane has a trade-off effect between high ion conductivity and dimensional stability, and is susceptible to hydroxide ions in high temperature and strong alkaline environments, resulting in a decrease in mechanical properties and making it difficult to take into account high ion conductivity and Chemical stability.
Using self-crosslinking polymers, a crosslinking network is formed by introducing fluorine atoms and flexible long alkyl side chains into the polymer, using Lewis acid to catalyze the Friedel-crafts alkylation and Menshutkin reaction, combining thermal crosslinking and electron beam irradiation. The process is performed to form an anion exchange membrane with an efficient ion transport channel.
While ensuring high ion conductivity, significantly improve the dimensional stability of the membrane, improve chemical stability and water retention capacity, it is suitable for fuel cells, electrolytic water and electrochemical reduction of carbon dioxide.
Smart Images

Figure CN119219873A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ion exchange membranes, and in particular relates to a self-crosslinking polymer and a preparation method thereof, an anion exchange membrane and applications thereof. Background Art
[0002] Anion exchange membrane (AEM) is an alkaline polyelectrolyte film. It contains alkaline functional groups, which can selectively transfer anions while also acting as a barrier. It is widely used in many fields such as water electrolysis, fuel cells, electrochemical reduction of carbon dioxide, and water treatment. The key indicators for evaluating the performance of anion exchange membranes include ion conductivity, dimensional stability, chemical stability, thermal stability, and mechanical stability. High ion exchange capacity often causes high swelling of the membrane, resulting in poor dimensional stability. Therefore, there is a trade-off effect between the ion conductivity and dimensional stability of the anion exchange membrane, which needs to be considered comprehensively in the membrane structure design. In addition, a high temperature and strong alkaline environment will make the anion exchange membrane vulnerable to attack by hydroxide ions, resulting in a decrease in the membrane's ion conductivity and mechanical properties. Therefore, the chemical stability of the anion exchange membrane is also crucial.
[0003] Polyarylene fluoroketone anion exchange membrane is obtained by superacid-catalyzed Friedel-crafts alkylation polycondensation of aromatic compounds and fluoroketone monomers, and then cationic functionalization by Menshutkin reaction. Polyarylene fluoroketone anion exchange membrane has advantages such as high ionic conductivity, excellent mechanical properties and chemical stability, but it also has the disadvantage of poor dimensional stability. Introducing a cross-linking agent to construct a cross-linked network is an effective strategy to improve its dimensional stability while maintaining high ionic conductivity. Chen Nanjun et al. introduced 4-vinylbenzyl chloride on the basis of polyarylene piperidine in "Chemically & Physically Stable Crosslinked Poly (aryl-co-arylpiperidinium)s for Anion Exchange Membrane Fuel Cells". The construction of the cross-linked network can effectively limit swelling and improve the overall working performance, but there are still some disadvantages. For example, the decrease in swelling of polyarylene piperidine membranes is mainly attributed to the decrease in ion exchange capacity (IEC) caused by the addition of cross-linking agents, and the water absorption rate and swelling rate decrease accordingly, but at the same time, the hydroxide ion conductivity also decreases significantly, and the trade-off effect between ionic conductivity and dimensional stability is still not overcome.
[0004] Therefore, developing new polymers based on existing technical solutions to prepare anion exchange membranes with high ionic conductivity, high size and chemical stability is of great significance to the development and application of anion exchange membranes. Summary of the invention
[0005] In order to overcome the defects of the prior art, the present invention provides a self-crosslinking polymer and a preparation method thereof, an anion exchange membrane and application thereof.
[0006] The first aspect of the present invention provides a self-crosslinking polymer, wherein the self-crosslinking polymer comprises a structural unit represented by formula I and a structural unit represented by formula II.
[0007]
[0008] Wherein, L1 and L2 are each independently selected from a C1-C10 alkylene group, R is selected from an alkylene group or an arylene group, Ar1 and Ar2 are each independently selected from an arylene group derived from an aromatic compound, and R1, R2, R3, R4, and R5 are each independently selected from H or a C1-C3 alkyl group.
[0009] According to the self-crosslinking polymer of the first aspect, based on the total molar number of the structural unit represented by formula I and the structural unit represented by formula II, the proportion of the structural unit represented by formula I is greater than or equal to 60%, and the proportion of the structural unit represented by formula II is less than or equal to 40%.
[0010] According to the self-crosslinking polymer of the first aspect, wherein R is selected from Wherein, p is an integer from 0 to 6;
[0011] Ar1 and Ar2 are each independently selected from:
[0012]
[0013]
[0014] wherein m is an integer of 0 to 6, n is an integer of 0 to 6, R6 and R7 are each independently selected from -H, -CH3, -Br or -Cl, preferably, m=n;
[0015] Preferably, L is pentylene, and R is Ar1 and Ar2 are R1, R2, R3, R4 and R5 are methyl groups.
[0016] The second aspect of the present invention provides a method for preparing the self-crosslinking polymer of the first aspect, comprising:
[0017] (1) contacting an aromatic compound with a trifluoroalkyl ketone under the action of a Lewis acid to obtain a precursor polymer, wherein the Lewis acid is preferably selected from one or more of trifluoromethanesulfonic acid, methanesulfonic acid, and trifluoroacetic acid, and more preferably trifluoromethanesulfonic acid;
[0018] Wherein, the aromatic compound has Ar1 and / or Ar2 structure, and the trifluoroalkyl ketone has the structure shown in formula III:
[0019]
[0020] Wherein, L has L1 and / or L2 structure;
[0021] Preferably, the weight average molecular weight of the precursor polymer obtained in step (1) is 20,000 to 500,000 g mol -1 , preferably 80,000 to 250,000 g mol -1 ;
[0022] (2) contacting the precursor polymer obtained in step (1) with a crosslinking monomer and a tertiary amine in sequence to obtain the self-crosslinking polymer;
[0023] Wherein, the cross-linking monomer has a structure shown in Formula IV:
[0024]
[0025] R is selected from Wherein, p is an integer from 0 to 6;
[0026] The tertiary amine is selected from one or more of trimethylamine, triethylamine and tripropylamine, preferably trimethylamine.
[0027] According to the method of the second aspect, in step (1), the molar ratio of the aromatic compound to the trifluoroalkyl ketone is 1:(1 to 1.2);
[0028] The contact temperature is 0 to 35°C; and / or
[0029] The contact time is 2 to 12 hours.
[0030] According to the method of the second aspect, in step (2), the molar ratio of the precursor polymer: the cross-linking monomer: the trimethylamine is 1: (0.1 to 0.4): (1.8 to 2.7); and / or
[0031] The contact temperature is 10 to 50° C. The contact time can be 12 to 72 hours.
[0032] According to the method of the second aspect, in step (1), the aromatic compound is contacted with the trifluoroalkyl ketone in a first solvent; preferably, the first solvent is an anhydrous solvent; and / or
[0033] In step (2), the precursor polymer is contacted with the crosslinking monomer and trimethylamine in a second solvent; preferably, the second solvent is selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0034] A third aspect of the present invention provides an anion exchange membrane, comprising:
[0035] The self-crosslinking polymer of the first aspect or the self-crosslinking polymer prepared according to the method of the second aspect is a crosslinked polymer formed by self-crosslinking reaction of its own unsaturated double bonds.
[0036] The fourth aspect of the present invention provides a method for preparing the anion exchange membrane of the third aspect, comprising:
[0037] (A) dissolving the self-crosslinking polymer of the first aspect or the self-crosslinking polymer prepared according to the method of the second aspect in a third solvent to obtain a casting solution;
[0038] (B) casting the casting solution prepared in step (A) into a film;
[0039] (C) subjecting the membrane obtained in step (B) to a thermal crosslinking treatment and / or an electron beam irradiation crosslinking treatment to obtain the anion exchange membrane.
[0040] According to the method of the fourth aspect, in step (A), the third solvent is selected from one or more of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide;
[0041] Preferably, in the casting solution, the mass ratio of the self-crosslinking polymer to the solvent volume is 0.015 to 0.40 g / mL.
[0042] According to the method of the fourth aspect, in step (B), the casting temperature is 50 to 80° C.;
[0043] In step (C), the thermal crosslinking treatment temperature is 70 to 150° C.; and / or
[0044] In step (C), the electron beam irradiation dose of the electron beam irradiation cross-linking treatment is 30 to 150 kGy.
[0045] The fifth aspect of the present invention provides the use of the self-crosslinking polymer of the first aspect, the self-crosslinking polymer prepared according to the method of the second aspect, the anion exchange membrane of the third aspect or the anion exchange membrane prepared according to the method of the fourth aspect in the fields of fuel cells, hydrogen production by electrolysis of water, and electrochemical reduction of carbon dioxide.
[0046] The self-crosslinking polymer of the present invention has but is not limited to the following beneficial effects:
[0047] The anion exchange membrane formed by in-situ self-crosslinking of the self-crosslinking polymer of the present invention can effectively limit swelling while ensuring high ion conductivity, and significantly improve the dimensional stability of the anion exchange membrane. The polymer and anion exchange membrane provided by the present invention have a green and simple synthesis method, low cost, and excellent performance, and can be widely used in fuel cells, water electrolysis, carbon dioxide electrochemical reduction and other fields, and have good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] The following drawings are intended to more clearly illustrate the technical solutions of the embodiments of the present application, and together with the specification, are used to explain the principles of the present application.
[0049] Figure 1 The precursor polymer in Example 1 of the present application is shown 1 H NMR spectrum.
[0050] Figure 2 The cross-linking monomer in Example 1 of the present application is shown 1 H NMR spectrum.
[0051] Figure 3 The ionic polymer in Example 1 of the present application is shown 1 H NMR spectrum.
[0052] Figure 4 An atomic force microscope image of the anion exchange membrane in Example 1 of the present application is shown.
[0053] Figure 5 The conductivity diagram of the anion exchange membrane in Example 1 of the present application is shown.
[0054] Figure 6 The polarization curve diagram of the anion exchange membrane electrolyzer in Example 1 of the present application is shown. DETAILED DESCRIPTION
[0055] The present application is further described in detail below through the accompanying drawings and embodiments. Through these descriptions, the characteristics and advantages of the present application will become clearer and more specific.
[0056] The word "exemplary" is used exclusively herein to mean "serving as an example, embodiment, or illustration." Any embodiment described herein as "exemplary" is not necessarily to be construed as preferred or advantageous over other embodiments. Although various aspects of the embodiments are shown in the drawings, the drawings are not necessarily drawn to scale unless otherwise noted.
[0057] In addition, the technical features involved in different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0058] The present invention provides a self-crosslinking polymer, comprising a structural unit shown in formula I and a structural unit shown in formula II,
[0059]
[0060] Wherein, L1 and L2 are each independently selected from a C1-C10 alkylene group, R is selected from an alkylene group or an arylene group, Ar1 and Ar2 are each independently selected from an arylene group derived from an aromatic compound, and R1, R2, R3, R4, and R5 are each independently selected from H or a C1-C3 alkyl group.
[0061] In one embodiment, based on the total molar number of the structural unit represented by Formula I and the structural unit represented by Formula II, the proportion of the structural unit represented by Formula I is greater than or equal to 60%, and the proportion of the structural unit represented by Formula II is less than or equal to 40%.
[0062] The self-crosslinking polymer of the present invention is composed of a fluorine-containing full carbon main chain, a flexible long alkyl side chain, and an in-situ crosslinking site of a double bond at the end of the side chain. The introduction of fluorine atoms can make the electronic effects on both sides of the ketone monomer differ more, which is conducive to improving the reaction activity and polymer molecular weight, and the strong hydrophobic property of fluorine atoms can significantly promote the effect of microphase separation in the membrane and improve the overall performance. The polymer skeleton does not contain heteroatoms, the cationic group is located at the end of the flexible side chain away from the main chain, and the flexible side chain provides steric hindrance for the cationic group, and has good chemical stability. At the same time, the flexible long alkyl chain is conducive to the migration of the terminal cationic group, which is conducive to ion transmission. In addition, due to the presence of double bond sites at the end of some long alkyl side chains, the polymer after high-temperature heat / irradiation treatment can undergo in-situ self-crosslinking, and the cationic group will aggregate with each other under the induction of double bonds and the action of flexible side chains, so that the hydrophilic group and the hydrophobic skeleton undergo hydrophilic and hydrophobic microphase separation, thereby forming an efficient ion transmission channel in the membrane and reducing the ion transmission resistance. Thereby, the anion exchange membrane formed by the self-crosslinking polymer of the present invention has good ion exchange performance, can be stably present for a long time under alkaline conditions, and has excellent water retention capacity and dimensional stability. The self-crosslinking polymer of the present invention may have repeating units of the following structure:
[0063]
[0064] Wherein, x and y represent the molar percentage of the corresponding segments in the total repeating units, x+y=1, and 0<y≤0.4.
[0065] In one embodiment, R is selected from Wherein, p is an integer from 0 to 6;
[0066] Ar1 and Ar2 are each independently selected from:
[0067]
[0068]
[0069] wherein m is an integer of 0 to 6, n is an integer of 0 to 6, R6 and R7 are each independently selected from -CH3, -Br or -Cl, preferably, m=n;
[0070] In one embodiment, L is pentylene, R is Ar1 and Ar2 are
[0071] In some specific embodiments, the repeating unit of the self-crosslinking polymer may be:
[0072]
[0073] The present invention also provides a method for preparing the self-crosslinking polymer, comprising:
[0074] (1) contacting an aromatic compound with a trifluoroalkyl ketone under the action of a Lewis acid to obtain a precursor polymer, wherein the Lewis acid is preferably selected from one or more of trifluoromethanesulfonic acid, methanesulfonic acid, and trifluoroacetic acid, for example, trifluoromethanesulfonic acid, a mixed acid of trifluoroacetic acid and trifluoromethanesulfonic acid, or a mixed acid of trifluoroacetic acid and methanesulfonic acid, and more preferably trifluoromethanesulfonic acid;
[0075] Wherein, the aromatic compound has Ar1 and / or Ar2 structure, and the trifluoroalkyl ketone has the structure shown in formula III:
[0076]
[0077] Wherein, L has L1 and / or L2 structure;
[0078] Preferably, the weight average molecular weight of the precursor polymer obtained in step (1) is 20,000 to 500,000 g mol -1 , preferably 80,000 to 250,000 g mol -1 ;
[0079] (2) contacting the precursor polymer obtained in step (1) with a crosslinking monomer and a tertiary amine in sequence to obtain the self-crosslinking polymer;
[0080] Wherein, the cross-linking monomer has a structure shown in Formula IV:
[0081]
[0082] R is selected from Wherein, p is an integer from 0 to 6;
[0083] The tertiary amine is selected from one or more of trimethylamine, triethylamine and tripropylamine, preferably trimethylamine.
[0084] The method of the present invention comprises the following steps: allowing an aromatic compound to undergo a Friedel-Crafts alkylation reaction with a trifluoroalkyl ketone under the action of trifluoromethanesulfonic acid to obtain a precursor polymer; specifically, the precursor polymer has the following structure:
[0085]
[0086] Wherein, Ar is Ar1 and / or Ar2 structure, q is the degree of polymerization of the precursor polymer, and q≥10; the precursor polymer is successively subjected to Menshutkin reaction with a cross-linking monomer and a trimethylamine solution to generate a cationic functional group, thereby obtaining the polymer.
[0087] In one embodiment, in step (1), the molar ratio of the aromatic compound to the trifluoroalkyl ketone is 1:(1-1.2);
[0088] The contact temperature is 0 to 35°C; and / or
[0089] The contact time is 2 to 12 hours.
[0090] In one embodiment, in step (2), the molar ratio of the precursor polymer::crosslinking monomer:trimethylamine is 1:(0.1-0.4):(1.8-2.7); and / or
[0091] The contact temperature is 10-50°C.
[0092] In one embodiment, in step (1), the aromatic compound is contacted with the trifluoroalkyl ketone in a first solvent; preferably, the first solvent is an anhydrous solvent, which is not particularly limited in the present invention, for example, the first solvent may be dichloromethane; and / or
[0093] In step (2), the precursor polymer is contacted with the crosslinking monomer and trimethylamine in a second solvent; preferably, the second solvent is selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide.
[0094] The present invention also provides an anion exchange membrane, comprising:
[0095] The self-crosslinking polymer or the self-crosslinking polymer prepared by the method described above is a crosslinking polymer formed by self-crosslinking reaction of its own unsaturated double bonds.
[0096] The end of some long alkyl side chains of the self-crosslinking polymer of the present invention has double bond sites, and the polymer after high-temperature heat / irradiation treatment can undergo in-situ self-crosslinking to form a crosslinked polymer and an anion exchange membrane.
[0097] In one embodiment, the method comprises:
[0098] (A) dissolving the aforementioned self-crosslinking polymer or the self-crosslinking polymer prepared according to the aforementioned method in a third solvent to obtain a casting solution;
[0099] (B) casting the casting solution prepared in step (A) into a film;
[0100] (C) subjecting the membrane obtained in step (B) to a thermal crosslinking treatment and / or an electron beam irradiation crosslinking treatment to obtain the anion exchange membrane.
[0101] In one embodiment, in step (A), the third solvent is selected from one or more of dimethyl sulfoxide, N-methylpyrrolidone, and N,N-dimethylformamide;
[0102] Preferably, in the casting solution, the mass ratio of the self-crosslinking polymer to the solvent volume is 0.015 to 0.40 g / mL.
[0103] In one embodiment, in step (B), the casting temperature is 50 to 80°C;
[0104] In step (C), the thermal crosslinking treatment temperature is 70 to 150° C.; and / or
[0105] In step (C), the electron beam irradiation dose of the electron beam irradiation cross-linking treatment is 30 to 150 kGy.
[0106] In a specific embodiment, the casting liquid is stirred and dissolved to prepare a homogeneous solution, which is then poured evenly onto a glass plate. After heating at 50 to 90° C. to evaporate the solvent, the membrane is carefully peeled off the glass plate and subjected to high-temperature heat treatment and / or irradiation treatment to allow the unsaturated double bonds in the polymer to self-crosslink to form a crosslinked network, thereby obtaining the self-crosslinking anion exchange membrane.
[0107] The present invention also provides the application of the aforementioned self-crosslinking polymer and anion exchange membrane in the fields of fuel cells, water electrolysis to produce hydrogen, and carbon dioxide electrochemical reduction.
[0108] The present invention has no special restrictions on the sources of all raw materials. Unless otherwise specified, they are all conventional products that can be obtained commercially.
[0109] In the following examples, the hydroxide ion conductivity was measured by the following method: the anion exchange membrane was cut into 1.0×5.0 cm regular strips and immersed in 1 M KOH solution for 24 h for OH- During the ion exchange, the alkali solution was replaced every 8 hours, rinsed and soaked in ultrapure water for 24 hours to remove the residual KOH solution. The sample was assembled in the conductivity test fixture, then placed in a glass bottle filled with ultrapure water and continuously flowed with N2. The experimental temperature was from 30℃ to 80℃, and the impedance of the anion exchange membrane was measured and recorded every 10℃ using a Princeton VersaSTAT 3F electrochemical workstation, and OH was calculated using formula (1) - Conductivity σ:
[0110] σ=L / (AR) (1)
[0111] Among them, A (cm 2 ) represents the membrane cross-sectional area calculated from the width and thickness of the membrane, L (cm) represents the distance between the electrodes, and R represents the ohmic resistance (R, kΩ) of the membrane at different temperatures (30°C to 80°C) under fully hydrated conditions.
[0112] The water absorption rate WU (%) and swelling rate SR (%) were measured as follows: the anion exchange membrane was cut into 3.0 × 3.0 cm samples and immersed in 1 M KOH solution for 24 h for OH - Ion replacement, during which the alkali solution was replaced every 8 hours, and then immersed in ultrapure water at 30℃ and 80℃ for 24 hours respectively. After taking out, wipe off the excess water on the surface, record the wet film mass and length, and mark them as W wet and L wet Afterwards, the anion exchange membrane was dried in a vacuum drying oven at 80°C, and the weight and length W of the membrane in the dry state were measured respectively. dry and L dry The water absorption rate and swelling rate at different temperatures are calculated by formulas (2) and (3):
[0113] WU(%)=(M wet -M dry ) / M dry ×100% (2)
[0114] SR(%)=(L wet -L dry ) / L dry ×100% (3)
[0115] The polarization curve is detected as follows: The AE01 (Jiamo Technology (Xiamen) Co., Ltd.) single electrolyzer test system measured that NiFe and Pt / C were used as catalysts for the anode and cathode, respectively. Before the test, AEI and AEM were pretreated by circulating 200mL of 1.0M KOH solution at 80°C for 3h, and the electrolyzer and corresponding pipeline system were repeatedly circulated with ultrapure water until washed to neutrality, and then 500mL of 0.2M KOH solution was circulated at 80°C for 3h for testing. In the polarization test, the battery output current and voltage were tested in a constant current mode, and the current density increased by 100mA / cm 2 , keep constant current charging for 30s, record the voltage value. When the battery voltage is higher than 2.2V, terminate the test, and the interval between two adjacent polarization curve tests should not be less than 0.5h.
[0116] polymer 1 H NMR spectra were obtained by Bruker AVANCE NEO 500, and Dimension FastScan atomic force microscopy was used to characterize the hydrophilic and hydrophobic microphase separation on the surface of anion exchange membranes.
[0117] Example 1
[0118] This example takes the synthesis and preparation of quaternary ammonium heat-treated self-crosslinked polybiphenyl fluoroketone anion exchange membrane VBN-25-PBPA-T in which the crosslinking group accounts for 25% of the polymer functional group as an example, wherein the selected trifluoroalkyl ketone for polymerization is 7-bromo-1,1,1-trifluoro-2-heptanone, and the crosslinking monomer is N-4-vinylphenyl-N,N-dimethylamine. The structural formula is as follows, wherein ρ is the degree of crosslinking, 0<ρ≤0.125:
[0119]
[0120] The specific preparation method comprises the following steps:
[0121] 1) Add 1.4g of biphenyl and 2.69g of 7-bromo-1,1,1-trifluoro-2-heptanone to a single-necked flask containing 6ml of the first solvent, anhydrous dichloromethane, wherein the molar ratio of biphenyl to 7-bromo-1,1,1-trifluoro-2-heptanone is 1:1.2. After stirring and dissolving evenly, add 6ml of trifluoromethanesulfonic acid, and react at room temperature for 2h. Transfer the precipitate after the reaction to methanol for washing, dry it, dissolve it in dichloromethane, precipitate it with methanol, wash it repeatedly three times, and dry it at 80°C to obtain a precursor polymer, the weight average molecular weight of the precursor polymer is M w 103870 g mol -1 The dispersion index PDI is 1.86. The precursor polymer prepared by the above method is used in the subsequent Examples 2-4. Figure 1 The precursor polymer PBPA-Br is shown1 H NMR spectrum.
[0122] 2) Precursor polymer: N-4-vinylphenyl-N,N-dimethylamine: trimethylamine = 1:0.25:2.25. Take 2g of the precursor polymer and dissolve it in 15ml of the second solvent N-methylpyrrolidone, then add 0.210g of N-4-vinylphenyl-N,N-dimethylamine, react at room temperature for 24h, then add 3ml of trimethylamine ethanol solution (30wt%) twice, and stir at room temperature for 6h each time. After the reaction is completed, precipitate with anhydrous ether and wash repeatedly three times, filter and vacuum dry at 30°C to obtain a quaternary ammonium ion polymer. Figure 2 The crosslinking monomer N-4-vinylphenyl-N,N-dimethylamine is shown. 1 H NMR spectrum. Figure 3 The ionic polymer 1 H NMR spectrum, where x=0.75 and y=0.25.
[0123] 3) Preparation of anion exchange membrane: Add 0.3g of the quaternary ammonium ion polymer obtained in step 2) to 15ml of the third solvent dimethyl sulfoxide, stir thoroughly for 12h to obtain a homogeneous casting solution, filter excess impurities using a PTFE filter with a pore size of 0.45μm, and then apply the casting solution on a clean and flat glass plate. After heating and evaporating the solvent dimethyl sulfoxide, a transparent film is obtained. After carefully peeling the film from the glass plate, place it under vacuum at 120℃ and dry it for 12h to allow the unsaturated double bonds in the membrane to fully self-crosslink. Soak the film in a 1M KOH solution for ion exchange. After soaking for 24h, wash the KOH with deionized water and soak it in deionized water for 24h to ensure that the remaining KOH can be removed, and obtain a quaternary ammonium self-crosslinked polybiphenyl fluoroketone anion exchange membrane VBN-25-PBPA-T with a thickness of 50μm.
[0124] The measured properties of the quaternary ammonium self-crosslinked polybiphenyl fluoroketone anion exchange membrane VBN-25-PBPA-T are shown in Table 1. The membrane was not degraded after being immersed in a 1M KOH solution at 80°C for 30 days, and the conductivity did not change significantly before and after the alkaline resistance test.
[0125] Figure 4 An atomic force microscope image of the anion exchange membrane VBN-25-PBPA-T is shown. Figure 5 Shown is a conductivity graph of the anion exchange membrane VBN-25-PBPA-T. Figure 6 The polarization curve diagram of the anion exchange membrane VBN-25-PBPA-T applied in the anion exchange membrane electrolyzer is shown.
[0126] Embodiment 2:
[0127] This embodiment provides a method for preparing a quaternized irradiation self-crosslinking polybiphenyl fluoroketone anion exchange membrane VBN-25-PBPA-R in which the ratio of crosslinking groups to polymer functional groups is 25%. It is basically the same as the preparation method in Example 1, except that in step 3), after the film is peeled off from the glass plate, it is placed under the action of an electron beam for irradiation, and the irradiation dose is 75 kGy, so that the unsaturated double bonds in the membrane are fully self-crosslinked.
[0128] The measured properties of VBN-25-PBPA-R are shown in Table 1. The membrane was not degraded after being immersed in a 1M KOH solution at 80°C for 30 days, and the conductivity did not change significantly before and after the alkaline resistance test.
[0129] Example 3
[0130] This embodiment provides a method for preparing a quaternary ammonium heat-treated self-crosslinked polybiphenyl fluoroketone anion exchange membrane VBN-10-PBPA-T in which the crosslinking group accounts for 10% of the polymer functional group. The structural formula is as follows, wherein ρ is the degree of crosslinking, 0<ρ≤0.05:
[0131]
[0132] It is basically the same as the preparation method in Example 1, except that in step 2), the precursor polymer: N-4-vinylphenyl-N,N-dimethylamine:trimethylamine=1:0.1:2.7, and the cross-linking ratio in the membrane is regulated by changing the feed ratio of the cross-linking monomer.
[0133] The measured performance of VBN-10-PBPA-T is shown in Table 1. The membrane was not degraded after being immersed in 1M KOH solution at 80°C for 30 days, and the conductivity did not change significantly before and after the alkaline resistance test.
[0134] Embodiment 4:
[0135] This embodiment provides a method for preparing a quaternized irradiation self-crosslinked polybiphenyl fluoroketone anion exchange membrane VBN-10-PBPA-R in which the ratio of crosslinking groups to polymer functional groups is 10%. It is basically the same as the preparation method in Example 3, except that in the preparation process of the anion exchange membrane, after the film is peeled off the glass plate, it is placed under the action of an electron beam for irradiation, and the irradiation dose is 75 kGy, so that the unsaturated double bonds in the membrane are fully self-crosslinked.
[0136] The measured properties of VBN-10-PBPA-R are shown in Table 1. The membrane was not degraded after being immersed in a 1M KOH solution at 80°C for 30 days, and the conductivity did not change significantly before and after the alkaline resistance test.
[0137] Embodiment 5:
[0138] This embodiment provides a method for preparing a quaternized heat-treated self-crosslinked polyaryl fluoroketone anion exchange membrane VBN-25-PFBA-T in which the crosslinking group accounts for 25% of the polymer functional group. The method is basically the same as the preparation method in Example 1, except that in the polymerization step of the precursor polymer in step 1), the aromatic compounds are selected as biphenyl and 9,9-dimethylfluorene, and the molar ratio of biphenyl:9,9-dimethylfluorene:7-bromo-1,1,1-trifluoro-2-heptanone is 0.25:0.75:1.1. The weight average molecular weight of the obtained precursor polymer is 92750 g mol -1 , the dispersion coefficient PDI is 2.06. By changing the composition of the main chain, the microstructure in the membrane can be regulated, which may include the following structure, where ρ is the cross-linking degree, 0<ρ≤0.125
[0139]
[0140]
[0141] The measured properties of VBN-25-PFBA-T are shown in Table 1. The membrane was not degraded after being immersed in a 1M KOH solution at 80°C for 30 days, and the conductivity did not change significantly before and after the alkaline resistance test.
[0142] Embodiment 6:
[0143] This embodiment provides a method for preparing a quaternized irradiation self-crosslinked polybiphenyl fluoroketone anion exchange membrane VBN-25-PFBA-R in which the ratio of crosslinking groups to polymer functional groups is 10%. It is basically the same as the preparation method in Example 5, except that in the preparation process of the anion exchange membrane, after the film is peeled off the glass plate, it is placed under the action of an electron beam for irradiation, and the irradiation dose is 75 kGy, so that the unsaturated double bonds in the membrane are fully self-crosslinked.
[0144] The measured properties of VBN-25-PFBA-R are shown in Table 1. The membrane was not degraded after being immersed in 1M KOH solution at 80°C for 30 days, and the conductivity did not change significantly before and after the alkaline resistance test.
[0145] The anion exchange membranes prepared in Examples 1-6 were subjected to OH treatment at 80°C. - The ionic conductivity, water absorption and swelling properties were tested, and the ion exchange capacity IEC was calculated. The results are shown in Table 1.
[0146] Table 1 Performance parameters of anion exchange membranes prepared in Examples 1-6
[0147]
[0148] As can be seen from Table 1, the anion exchange membranes prepared in Examples 1-6 of the present invention exhibited excellent ion exchange performance at different temperatures, and also had excellent water retention capacity and dimensional stability. The ion exchange membranes of the present invention have high stability under alkaline conditions, and there is no degradation after being immersed in a 1M KOH solution at 80°C for 30 days. There is no significant change in conductivity before and after the alkaline resistance test, and the membranes can be stably present for a long time in an alkaline environment.
[0149] The present application has been described above in conjunction with preferred embodiments, but these embodiments are only exemplary and serve only as an illustration. On this basis, various replacements and improvements may be made to the present application, all of which fall within the scope of protection of the present application.
Claims
1. A self-crosslinking polymer, comprising a structural unit represented by formula I and a structural unit represented by formula II, in, L1 and L2 are each independently selected from a C1-C10 alkylene group, R is selected from an alkylene group or an arylene group, Ar1 and Ar2 are each independently selected from an arylene group derived from an aromatic compound, and R1, R2, R3, R4, and R5 are each independently selected from H or a C1-C3 alkyl group.
2. The self-crosslinking polymer according to claim 1, characterized in that Based on the total molar number of the structural unit represented by Formula I and the structural unit represented by Formula II, the proportion of the structural unit represented by Formula I is greater than or equal to 60%, and the proportion of the structural unit represented by Formula II is less than or equal to 40%.
3. The self-crosslinking polymer according to claim 1, characterized in that R is selected from Wherein, p is an integer from 0 to 6; Ar1 and Ar2 are each independently selected from: wherein m is an integer of 0 to 6, n is an integer of 0 to 6, R6 and R7 are each independently selected from -H, -CH3, -Br or -Cl, preferably, m=n; Preferably, L is pentylene, and R is Ar1 and Ar2 are and / or R1, R2, R3, R4 and R5 are methyl groups.
4. The method for preparing a self-crosslinking polymer according to any one of claims 1 to 3, characterized in that: The method comprises: (1) contacting an aromatic compound with a trifluoroalkyl ketone under the action of a Lewis acid to obtain a precursor polymer, wherein the Lewis acid is preferably selected from one or more of trifluoromethanesulfonic acid, methanesulfonic acid, and trifluoroacetic acid, and more preferably trifluoromethanesulfonic acid; Wherein, the aromatic compound has Ar1 and / or Ar2 structure, and the trifluoroalkyl ketone has the structure shown in formula III: Wherein, L has L1 and / or L2 structure; Preferably, the weight average molecular weight of the precursor polymer obtained in step (1) is 20,000 to 500,000 g mol -1 , preferably 80,000 to 250,000 g mol -1 ; (2) contacting the precursor polymer obtained in step (1) with a crosslinking monomer and a tertiary amine in sequence to obtain the self-crosslinking polymer; Wherein, the cross-linking monomer has a structure shown in Formula IV: R is selected from Wherein, p is an integer from 0 to 6; The tertiary amine is selected from one or more of trimethylamine, triethylamine and tripropylamine, preferably trimethylamine.
5. The method according to claim 4, characterized in that In step (1), the molar ratio of the aromatic compound to the trifluoroalkyl ketone is 1:(1-1.2); The contact temperature is 0 to 35°C; and / or The contact time is 2 to 12 hours.
6. The method according to claim 4, characterized in that In step (2), the molar ratio of the precursor polymer: the cross-linking monomer: the trimethylamine is 1: (0.1-0.4): (1.8-2.7); and / or The contact temperature is 10 to 50° C. The contact time is 12 to 72 hours.
7. The method according to claim 4, characterized in that In step (1), the aromatic compound is contacted with the trifluoroalkyl ketone in a first solvent; preferably, the first solvent is an anhydrous solvent; and / or In step (2), the precursor polymer is contacted with the crosslinking monomer and trimethylamine in a second solvent; preferably, the second solvent is selected from one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, and N,N-dimethylacetamide.
8. An anion exchange membrane comprising: The self-crosslinking polymer according to claim 1 or 2 or the self-crosslinking polymer prepared by the method according to any one of claims 3 to 7 is a crosslinked polymer formed by self-crosslinking reaction of its own unsaturated double bonds.
9. The method for preparing an anion exchange membrane according to claim 8, characterized in that: The method comprises: (A) dissolving the self-crosslinking polymer according to claim 1 or 2 or the self-crosslinking polymer prepared by the method according to any one of claims 3 to 7 in a third solvent to obtain a casting solution; (B) casting the casting solution prepared in step (A) into a film; (C) subjecting the membrane obtained in step (B) to a thermal crosslinking treatment and / or an electron beam irradiation crosslinking treatment to obtain the anion exchange membrane.
10. The method according to claim 9, characterized in that In step (A), the third solvent is selected from one or more of dimethyl sulfoxide, N-methylpyrrolidone, N,N-dimethylformamide, and N,N-dimethylacetamide; Preferably, in the casting solution, the mass ratio of the self-crosslinking polymer to the solvent volume is 0.015 to 0.40 g / mL.
11. The method according to claim 9, characterized in that In step (B), the casting temperature is 50-80°C; In step (C), the thermal crosslinking treatment temperature is 70 to 150° C.; and / or In step (C), the electron beam irradiation dose of the electron beam irradiation cross-linking treatment is 30 to 150 kGy.
12. Use of the self-crosslinking polymer according to claim 1 or 2, the self-crosslinking polymer prepared by the method according to any one of claims 3 to 7, the anion exchange membrane according to claim 8, or the anion exchange membrane prepared by the method according to any one of claims 9 to 11 in the fields of fuel cells, hydrogen production by electrolysis of water, and electrochemical reduction of carbon dioxide.
Citation Information
Patent Citations
Polymer, anion exchange membrane and preparation method and application thereof
CN116478377A
Polyarylene ion exchange membrane and preparation method thereof
CN117866264A
Cross-linked polymer as well as preparation method and application thereof
CN118255970A
Device for manufacturing a material of gelatin capsule
KR102089391B1
Anion exchange membrane and method for manufacturing same
WO2024039146A1
Cited By
Preparation method and application of anion exchange membrane
CN121226820A
Beta-H-free diamino anion exchange membrane as well as preparation method and application thereof
CN122277833A